Report for the draft laws on 1. organization of government (14 draft) an 2 the electon of Deputies to The Natinonal Assemmbly and to the people councils of Viet Nam. - Dr. Penelopa Gjurchilova (2015)
Toàn văn Báo cáo cho dự thảo luật về Luât Tổ chức chính phủ (14 dự thảo) một Luật đại biểu của Đại biểu Quốc hội và Hội đồng nhân dân của Việt Nam.